Optimum In-row Distance for Eggplant Production and Economic Returns - Bielinski M. Santos (EDIS)
HS-1115, a 3-page illustrated fact sheet by Bielinski M. Santos, presents the results of research to determine appropriate in-row distances for eggplant in Florida and to determine the best economic returns of this practice. Published by the UF Department of Horticultural Sciences, May 2007.